The Expression of Homo Sapiens microRNA-21 (Hsa-miR-21-5p) and mRNA Reversion Inducing Cysteine Rich Protein with Kazal Motifs (RECK) in Plasma of Epithelial Ovarian Cancer - Aprilia Indra Kartika; SN Chasanah; AS Fitriawan; DS Tanjung; MS Ftria; FK Pakun; R Oktriani; A Trirahmanto; H Prajatmo; T Aryandono; SM Haryana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
ABSTRACT Epithelial Ovarian Cancer (EOC) is malignant cancer that caused death for most women in Indonesia. The emergence of EOC showed no specific symptoms in its early stages; that makes the screening mostly occur when patients are in advanced stage. Treatment of EOC at an advanced stage will be more challenging with poor prognosis. Therefore, minimally invasive biomarkers are needed to diagnose at the early stage. microRNA is one of the potential biomarkers which not only expressed inside the cell but also secreted outside the cell with exosome protection. This protection makes microRNA stable. Moreover, several studies have shown the ability to detect microRNA in the blood sample. microRNA-21 (miR-21) is oncomiR which targeted tumor suppressor mRNA RECK based on in silico analysis.The first aim is to determine the expression of miR-21 in plasma samples of EOC patients compared with healthy controls. The second aim is to investigate the expression correlation between miR-21 and RECK mRNA.Blood samples were collected from 30 patients and 30 healthy controls. Plasma was then obtained from centrifugated blood samples. The total RNA was isolated and reverse transcribed to produce cDNAs. cDNAs were then quantified using qPCR using specific primer for miR-21 and RECK mRNA. The expression analysis was done relative expression method by Livak. The expression of miR-21 was calculated using the miR-16 expression as the reference gene. Also, Beta-actin was used as reference gene for RECK mRNA calculation. The correlation between the expression of miR-21 and mRNA RECK was analyzed using the Spearman rho correlation analysis.In this study showed the expression of miR-21 in patients with EOC increased 4.7579-fold compared with healthy controls (p <0.05). On the other hand, the miR-21 target, RECK mRNA, decreased 4,2 times with fold change 0.237665 on plasma EOC patients compared with healthy controls (p <0.05). The statistical calculation of the expression of miR-21 and mRNA RECK was inversely proportional to mRNA RECK with a strong correlationThis study has been able to prove that the expression of miR-21 is up-regulated in EOC patients and confirmed by the down-regulation of RECK expression. The next research challenge is to make anti-miR-21 to suppress the expression of miR-21 in EOC, which can be analyzed the effect of miR-21 in the development of EOC.